KEEFEKTIFAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA KELAS V MI NURUL AMANAH KABUPATEN GROBOGAN - Fitria Kalifah; Muhammad Arief Budiman; Suyitno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This type of research is quantitative research in the form of a pre-experimental design using a one-group pre-test-post-test design. The purpose of this study was to determine the effectiveness of audio-visual media on English learning outcomes for fifth grade students of MI Nurul Amanah. The results of the research conducted indicate that audio-visual media affect the learning outcomes of English subjects. This study was measured by student learning outcomes in English subjects when participating in the learning process or during the pre-test and post-test. Based on the calculation results, the pre-test score showed an average of 40.8 and the post-test score showed an average of 86.67. Therefore, student learning outcomes increased by 45.87 from a given KKM of 70. The effectiveness of video-based audio-visual media for students in the classroom supports the learning process when students are very involved and interested in participating in the learning process, making the learning process interesting and active. The media can improve student learning outcomes. This is evidenced by students being more actively involved in discussions, creating projects from their own ideas and creativity, and putting them into works to be presented in class. The conclusion obtained from the results of this study is that the application process of audio-visual media in learning English makes it easier for students to understand the material, remember the material, explore their creativity, and improve their learning outcomes.